ANALYSIS OF DETERMINANTS OF EXPOSURE TIME FOR LIQUIDATION VALUE AT THE PUBLIC APPRAISAL SERVICE OFFICE IN MEDAN CITY - Arbi Qirara M. Purba; Sugiharto Pujangkoro; Nazaruddin Nazaruddin (Bajang Institute, 2022)
The purpose of this research is to understand analysis of determinants of exposure time for liquidation value at the Public Appraisal Service Office in Medan City. This research is a correlationresearch. The population in this study are all the Public Appraisal Service Office in Medan City. Based on information as of April 17, 2020 from the Financial Professional Development Center, the number of the Public Appraisal Service Offices in Medan City is 28 offices. The method used in this sampling is saturated sampling. Researchers took the same number of samples as the population or called a census, namely the Public Appraisal Service Office in Medan City, represented by 3 appraisers from 1 the Public Appraisal Service Office in Medan City with a total sample of 84 people. The analysis method uses t-statistics (bootstrapping). The results show that location of the object has a positive and significant effect on exposure time for liquidation value at the Public Appraisal Service Office in Medan City. Type has a positive and significant effect on exposure time for liquidation value at the Public Appraisal Service Office in Medan City. Function or condition has a positive and not significant effect on exposure time for liquidation value at the Public Appraisal Service Office in Medan City. Market condition has a positive and not significant effect on exposure time for liquidation value at the Public Appraisal Service Office in Medan City.